Evaluation of disease severity in bronchiectasis using impulse oscillometry. Issue 4 (13th October 2020) - Yamamoto, Yuji; Miki, Keisuke; Tsujino, Kazuyuki; Kuge, Tomoki; Matsuki, Takanori; Fukushima, Kiyoharu; Oshitani, Yohei; Kagawa, Hiroyuki; Yoshimura, Kenji; Miki, Mari; Kida, Hiroshi
Although the diagnostic value of impulse oscillometry (IOS) in bronchiectasis for the differential diagnosis of healthy subjects has been researched, the usefulness of each IOS parameter for predicting disease severity in bronchiectasis has not been thoroughly investigated. In addition, the usefulness of IOS in patients with nontuberculous mycobacteria (NTM) infection has not been reported. This study aimed to determine the predictive significance of respiratory impedance and detect the other most significant IOS parameters for predicting disease severity in bronchiectasis patients and to validate the usefulness of IOS in patients with NTM infection. A total of 206 patients with bronchiectasis who attended clinics at the National Hospital Organization Osaka Toneyama Medical Center were included. Chest high-resolution computed tomography, spirometry and IOS were performed. Hospital admissions, mortality and disease severity indices for bronchiectasis (Bronchiectasis Severity Index (BSI), FACED, and E-FACED scores) were calculated to assess disease severity. The patients were divided into subgroups with and without NTM infection, and subgroup analyses were performed. Respiratory reactance, especially resonant frequency ( f res ), correlated with both BSI and FACED score better than respiratory resistance. Inspiratory but not expiratory impedance was strongly correlated with BSI, FACED and E-FACED scores. Inspiratory f res was the most useful predictor, increasing as the disease became more severe. The usefulness of IOS was almost equivalent in patients both with and without NTM infection. Inspiratory reactance measured by IOS is useful for estimating disease severity in bronchiectasis. Inspiratory f res best predicts disease severity in bronchiectasis patients both with and without NTM infection. Inspiratory reactance measured by impulse oscillometry may be useful for estimating disease severity of bronchiectasis. Inspiratory f res can be used to evaluate severity in the disease both with and without NTM infection. https://bit.ly/3fvG0Rn